Lowering of brain endothelial cell barrier function by exposure to 4′-iodo-α-pyrrolidinononanophenone. (1st September 2022) - Sakai, Yuji; Taguchi, Maki; Morikawa, Yoshifumi; Suenami, Koichi; Yanase, Emiko; Takayama, Tomohiro; Ikari, Akira; Matsunaga, Toshiyuki
Abstract: Overuse of pyrrolidinophenones (PPs) is known to cause damage to vascular and central nervous systems, but little is known about its effect on brain endothelial barrier function. In this study, we found that exposure to 4′-iodo-α-pyrrolidinononanophenone (I-α-PNP), one of the most potently cytotoxic PPs, at sublethal concentrations decreases trans -endothelial electrical resistance and increases paracellular permeability across a monolayer of human brain microvascular endothelial cells. Treatment with I-α-PNP also elevated the production of superoxide anion. Furthermore, the treatment reduced the expression and plasma membrane localization of a tight junction protein claudin-5 (CLDN5), which was almost restored by pretreatment with an antioxidant N -acetyl-l -cysteine. These results indicate that I-α-PNP treatment may down-regulate the plasma membrane-localized CLDN5 by elevating the production of reactive oxygen species (ROS). The treatment with I-α-PNP increased the nuclear translocation of Forkhead box protein O1 (FoxO1), an oxidative stress-responsive transcription factor, and pretreating with a FoxO1 inhibitor ameliorated the decrease in CLDN5 mRNA. In addition, I-α-PNP treatment up-regulated the expression and secretion of matrix metalloproteinase-2 (MMP2) and MMP9, and the addition of an MMP inhibitor reversed the degradation of CLDN5 by I-α-PNP. Moreover, I-α-PNP treatment facilitated the activation of 26S proteasome-based proteolytic activity and pretreatment with an inhibitor of 26S proteasome, but not autophagy, suppressed the CLDN5 degradation by I-α-PNP. Accordingly, it is suggested that the down-regulation of CLDN5 by exposure to I-α-PNP is ascribable to suppression of the gene transcription due to FoxO1 nuclear translocation through ROS production and to acceleration both of the MMPs (MMP2 and MMP9)- and 26S proteasome-based proteolysis. Graphical abstract: Image 1 Highlights: 4′-Iodo-α-pyrrolidinononanophenone (I-α-PNP) disrupts endothelial cell barrier. I-α-PNP reduces the expression of plasma membrane-localized claudin-5 (CLDN5). The ROS production by I-α-PNP decreases the transcription and expression of CLDN5. Metalloproteinases and proteasome are also involved in the CLDN5 down-regulation.